A comprehensive review of the S-N fatigue behaviour of adhesive joints - F.Castro Sousa; P. Zamani; A. Akhavan-Safar; L.F.M. da Silva (Journal of Advanced Joining Processes, 2024)
The complex fatigue failure mechanisms render it challenging to arrive at definitive conclusions regarding the behaviour of adhesive joints under cyclic loading. The goal of this review paper is to compile the various research conducted in this field and offer insights into the S-N fatigue response of adhesive joints. This review delves into experimental studies that investigate different factors influencing the fatigue life of bonded structures, encompassing joint geometry, environmental conditions, and loading conditions. Subsequently, the various approaches to improve the fatigue performance and durability of bonded joints are explored. It also examines S-N based life prediction methods, analysing their merits and limitations in assessing the fatigue life of adhesive joints under different conditions. In addition, this review pays attention to studies that focus on real bonded joints. It highlights the importance of bridging the gap between simplified conditions and real-world performance to ensure the durability and safety of bonded joints under service conditions.The review demonstrates that factors such as adhesive/adherend thickness, fillet, and overlap shape (e.g., wavy pattern, step, scarf) do impact fatigue life. However, the critical role played by overlap length in the fatigue life of bonded joints stands out. Improving fatigue life through adjustments, such as adhesive/adherend thickness, depends on the specific case. Therefore, further investigations are warranted in this area. The review suggests that carbon family nanoparticles can enhance bonded joint fatigue strength. Hybrid reinforcement with carbon and organic nanoparticles, like silica, offers a cost-effective path to improve joint life. Regarding life prediction, there is currently no universal fatigue model that considers all parameters impacting the fatigue life of adhesive joints. Fatigue analysis methods considered for real adhesive joints vary between sectors. Initial designs frequently employ indirect fatigue life assessment methods, yet direct fatigue analysis through testing actual joints remains essential for ensuring reliability.